Dignity Through Mobility : Human Rights and the Implementation of Inclusive Tourism in Bandung - Kanigara Hawari; Taufik, Giri; Widyastuti (Universitas Djuanda, 2026)
Freedom of tourism, the ability to travel, enjoy leisure, and access destinations, is a fundamental right that should be enjoyed by all individuals, including persons with disabilities. This study evaluates the inclusivity of tourism policies in Bandung City from a human rights perspective, using a socio-legal approach. Normatively, we analyze international and domestic legal frameworks (the UN Convention on the Rights of Persons with Disabilities, Indonesia’s laws on tourism and disability, and Bandung’s regional policies) to assess commitments to inclusive tourism. In addition to the normative approach, this study also uses on-site observations at three representative tourist destinations in Bandung, namely the heritage district of Jalan Braga, the civic and museum area around Gedung Sate, and the cultural attraction Saung Angklung Udjo. The observations examine the availability and quality of sitest that implement universal design principles, with particular attention to accessibility for persons with disabilities. Results indicate that Bandung’s Tourism Development Master Plan (RIPPARDA 2012–2025) and related policies and regulations formally recognize the equal rights of persons with disabilities to travel and participate in tourism. Concrete steps towards inclusive tourism are evident, such as the installation of ramps, tactile guiding blocks, braille signage, and accessible toilets at major sites. However, gaps remain between policy and practice, as evident in the three on-sites visit, some facilities are inconsistently provided or poorly maintained, and accessibility standards are not uniformly enforced, limiting full realization of “tourism for all”. The study concludes with several recommendations to strengthen both policy/regulations and their implementation. Key areas need to be strengthened are, enhancing local regulations, improving infrastructure, staff training, multi-stakeholder partnerships, and accessible information systems, to bolster implementation of inclusive tourism and ensure that the right to tourism is fulfilled for everyone. This research contributes to a deeper understanding of how urban tourism development can uphold human rights and sustainability principles by being genuinely inclusive.